Extracellular and cell-bound verocytotoxins of Salmonella serovars - SINGH, Y; SHARMA, V D; CHANDRA, R; GARG, S K (The Indian Journal of Animal Sciences, 2013)
The 27 strains of Salmonella belonging to 9 different serovars, namely S. Enterica sub. sp. Enterica serovar Newport, S. stanley, S. weltevreden, S. typhimurium, S. senftenberg, S. agona, S. bareilly, S. braenderup and S. kentucky isolated from foods of animal origin, were tested for their cytotoxicity on Vera cell-line. The cell sonicates of all the 27 strains of Salmonella showed variable degree of cytotoxicity, while 25 CFCS (92.5%) of these strains were found cytotoxic to Vero cells. The intensity of changes in Vero cells appeared to be dose dependent and increased irreversibly with increase in incubation period. Polymyxin B sulphate (@0.25 mglml in PBS, pH 7.2), urea (8 M in tris-HCI buffer, pH 8.2) and cell -sonication facilitated the release of cytotoxin.